Adsorbate-driven dynamic active sites in stannosilicate zeolites - Xianfeng Yi; Yao Xiao; Changjiu Xia; Fengqing Liu; Yujia Liu; Yu Hui; Xin Yu; Yucai Qin; Wei Chen; Zhiqiang Liu; Lijuan Song; Anmin Zheng (Fundamental Research)
Elucidating the nature of the active sites in heterogeneous catalysts is fundamental for understanding their reactivity and catalytic performances. Although stannosilicate zeolites have tremendous application potential for catalyzing biomass-related compounds in aqueous media, the detailed local structures and features of the real active sites and their possible structural variations under reaction conditions are poorly understood to date. In this study, a dynamic transformation of framework Sn−O−Si sites to Sn−OH/Si−OH pairs and subsequently a pseudo-Brønsted acid in stannosilicate zeolites upon molecular adsorption, which is analogous to various adsorbates/reactants under working conditions, was identified by solid-state nuclear magnetic resonance (NMR) spectroscopy for the first time, which challenges the widespread assumption that the active center structures remain rigid/stable during the catalytic process. These results provide new comprehensive insights for the fundamental understanding of the dynamic and flexible active centers and involved reaction mechanisms of novel zeolite catalysts with heterometal atoms, such as Sn, Ti, and Zr.